The impact of South African business on employment relations in Mozambique: a case study of Banco Austral, a subsidiary of ABSA - Mtyingizana, Beata Nontlahla (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
This thesis examines the impact of South African business on employment relations in Mozambique. The study specifically focuses on a case study of Banco Austral, a subsidiary of the Amalgamated Banks of South Africa (ABSA), to provide a richer and deeper analysis of employment practices. The study examines the extent to which the expansion of South African businesses in Mozambique has influenced the development of employment relations there. It examines whether the employment relations that exist at Banco Austral are a direct result of the influence of its parent firm, ABSA. It assesses whether the prevailing managerial practices at Banco Austral are distinctly local and a product of Mozambican history or whether the employer and employee relations that exist in that bank are an outcome of some form of hybridised host country and parent firm practices. The study is contextualised within the period of transition that both countries underwent. In the South African context, the end of apartheid promised political stability, democracy and racial harmony. It facilitated South Africa's reinsertion into the international economy and enabled its investors to embark on large-scale penetration of potential markets. It also opened up opportunities for investors to take advantage of the new global order in the rest of Africa and particularly in Mozambique. Similarly, in Mozambique, the transition to capitalism and to liberal democracy in 1994 marked a clear shift of policy from an authoritarian one-party state characterised by a planned socialist economy. In embracing a liberal market economy, Mozambique facilitated a transference of ownership of major state assets to the private sector and opened itself to the private sector's market-driven business practices and managerial cultures. The study found that the impact of these historical developments on the evolution of employment relations at Banco Austral has been contradictory. ABSA's ownership of Banco Austral opened as many opportunities as it closed them. On the one hand, it marked an opportunity for the growth and development of the ABSA brand across Mozambique. It presented opportunities for the integration of the Mozambican workforce into the larger ABSA Group and thereby enabling the transference of innovative managerial practices, world class human resources management techniques and advanced banking technology from ABSA and into Banco Austral. ABSA's acquisition of Banco Austral also opened prospects for the development of skills for the workforce, enhanced the chances of job mobility as well as opened opportunities for Banco Austral workers to take advantage of the newly created jobs. On the other hand, however, the managerial practices and the human resource management techniques transferred from ABSA was reported by Banco Austral workers to be far from innovative. Instead, they resembled traits of past practices characteristic of Mozambique's colonial workplace regime and South Africa's apartheid workplace regime. This tilted the balance of power in favour of managers who arbitrarily exercised their authority in ways similar to that of the Portuguese managers in colonial Mozambique and that of the production councils during the post-independence socialist period. Access to senior positions and training opportunities continued to be allocated along national and racial lines. Many Mozambican workers were said to be ABSA-unfit and could not be trained in critical areas to improve their relevance in the larger ABSA Group. Despite these findings however, this study shows that Banco Austral workers were not helpless actors in the employment relationship. Rather, they remained agents of change in their own right, endowed with varying degrees of power, which they used to minimise the impact of arbitrary management practices and influence the direction of the employment relationship to advance their interests. The argument of this thesis is advanced by locating the study within Pierre Bourdieu's theoretical triad of capital, field and habitus. Bourdieu's theoretical triad is used as important analytical tools for understanding how ABSA-specific practices evolved and continued to shape the conduct and thoughts of its managers and workers alike. This study also makes special contribution to Marxism by revisiting Marx's conception of the labour process to expose a number of analytical dilemmas when Marx is applied to bank labour.
Keywords: Industrial sociology -- Mozambique; Industrial relations -- Mozambique; Industrial relations -- Cross-cultural studies; Industrial sociology -- Political aspects; Personnel management -- Mozambique; Personnel management -- Political aspects; ABSA Bank; Banco Austral